Rooftop Turbine Ventilator performance for Terrace House in Malaysia (International Journal of Architecture and Urbanism, 2025)
This study evaluates the effectiveness of a Rooftop Turbine Ventilator (RTV) in expelling hot air from the attic and reducing heat accumulation in a terraced house in Malaysia. By integrating the RTV with natural ventilation, the system improves indoor air quality and reduces dependency on air-conditioning, consequently lowering energy consumption. The RTV operates as a form of wind-assisted stack ventilation, relying on the pressure difference between indoor and outdoor air to generate airflow through the building's openings. While wind-driven ventilation may be less reliable in densely packed terraced house areas, the stack effect, which requires lower air intakes and taller building heights, is more effective. However, while this stack effect can aid natural ventilation, it can also introduce hot and humid tropical air into the building. Therefore, a balanced design is necessary to manage temperature and humidity effectively. This paper provides a preliminary investigation into the role of RTV in enhancing stack ventilation within a terraced housing unit.